Social Entrepreneurship and Migrants' Inclusion Insights from the Adriatic-Ionian Region - Bianchini, Stefano; Bandini, Federica; Bolzani, Daniela (Sustainable Development Goals Series, 2024)
XXXIII, 314 p. 21 illus.